Effect of body mass index on operative outcome after robotic-assisted Ivor-Lewis esophagectomy: retrospective analysis of 129 cases at a single high-volume tertiary care center. Issue 1 (21st December 2016) - Salem, Ahmed I.; Thau, Matthew R.; Strom, Tobin J.; Abbott, Andrea M.; Saeed, Nadia; Almhanna, Khaldoun; Hoffe, Sarah E.; Shridhar, Ravi; Karl, Richard C.; Meredith, Kenneth L.
SUMMARY: The impact of body weight on outcomes after robotic-assisted esophageal surgery for cancer has not been studied. We examined the short-term operative outcomes in patients according to their body mass index following robotic-assisted Ivor-Lewis esophagectomy at a high-volume tertiary-care referral cancer center and evaluated the safety of robotic surgery in patients with an elevated body mass index. A retrospective review of all patients who underwent robotic-assisted Ivor-Lewis esophagectomy between April 2010 and June 2013 for pathologically confirmed distal esophageal cancer was conducted. Patient demographics, clinicopathologic data, and operative outcomes were collected. We stratified body mass index at admission for surgery according to World Health Organization criteria; normal range is defined as a body mass index range of 18.5–24.9 kg/m 2 . Overweight is defined as a body mass index range of 25.0–29.9 kg/m 2 and obesity is defined as a body mass index of 30 kg/m 2 and above. Statistics were calculated using Pearson's Chi-square and Pearson's correlation coefficient tests with a P -value of 0.05 or less for significance. One hundred and twenty-nine patients (103 men, 26 women) with median age of 67 (30–84) years were included. The majority of patients, 76% ( N  = 98) received neoadjuvant therapy. When stratified by body mass index, 28 (22%) were normal weight, 56 (43%) were overweight, and 45 (35%) were obese. All patients had R0 resection. Median operating room time was 407 (239–694) minutes. When stratified by body mass index, medians of operating room time across the normal weight, overweight and obese groups were 387 (254–660) minutes, 395 (310–645) minutes and 445 (239–694), respectively. Median estimated blood loss (EBL) was 150 (25–600) cc. When stratified by body mass index, medians of EBL across the normal weight, overweight and obese groups were 100 (50–500) cc, 150 (25–600) cc and 150 (25–600), respectively. Obesity significantly correlated with longer operating room time ( P  = 0.05) but without significant increased EBL ( P  = 0.348). Among the three body mass index groups there was no difference in postoperative complications including thrombotic events (pulmonary embolism and deep venous thrombosis) ( P  = 0.266), pneumonia ( P  = 0.189), anastomotic leak ( P  = 0.090), wound infection ( P  = 0.390), any cardiac events ( P  = 0.793) or 30 days mortality ( P  = 0.414). Our data study demonstrates that patients with esophageal cancer and an elevated body mass index undergoing robotic-assisted Ivor-Lewis esophagectomy have increased operative times but no significantly increased EBL during the procedure. Other potential morbidities did not differ with the robotic approach.